Biodegradable polymeric micelle-encapsulated doxorubicin suppresses tumor metastasis by killing circulating tumor cells. Issue 12 (28th March 2015) - Deng, Senyi; Wu, Qinjie; Zhao, Yuwei; Zheng, Xin; Wu, Ni; Pang, Jing; Li, Xuejing; Bi, Cheng; Liu, Xinyu; Yang, Li; Liu, Lei; Su, Weijun; et al.
<x xml:space="preserve">Abstract</x> Doxorubicin (Dox) micelles showed improved anti-metastasis activity by killing circulating tumor cells (CTCs) in zebrafish and mouse models, which may have potential applications in cancer therapy.